Comunicación, violencia y poder simbólico en la sociología de Pierre Bourdieu - Silva Echeto, Víctor Manuel; Browne Sartori, Rodrigo (Nómadas. Critical Journal of Social and Juridical Science, 2008)
Pierre Bourdieu dialogued with and wandered around different disciplines defending the transverse nature of the Social Sciences. His permanent concern over the place of the “sociology of sciences” led him to develop a theoretical programme of study that will suppose the “autonomy” of the “scientific field”. Starting from his works about “the distinction” and the tastes focused from the constitution of the habitus (as structurant structures that dismantle the structured structures), passing through his studies in the scientific field, and arriving at his last concerns about the communication media –mainly the journalistic function of television-, Bourdieu pointed out the importance of the intellectuals’ role, considering a rethinking of the notions exposed in relation to the symbolic issue, in which some specific concepts appear as example, as those of power and symbolic violence.